Pengembangan Bahan Ajar Kemampuan Pemahaman Matematis Siswa pada materi Fungsi Dengan Model Pembelajaran Problem based Learning - Maharani, Anggita (Penerbit STKIP PGRI Bangkalan, 2019)
The objectives of this research were to, (1) find out The Development of Learning Material after being implemented to the students of class VIII Junior High School based on Students’ Mathematics Comprehension Ability with using Problem Based Learning teaching style at the function lesson of class VIII which was valid then being analyzed and described. This research also aimed to, (2) find out the students’ score limit of each student viewed from School’s Limit Score, it was 75. The methods were used in this research were qualitative and quantitative methods, the qualitative method was to analyze limited trial on questions of Mathematics Comprehension Instrument Ability after the module of lesson material was being validated, whereas the quantitative method was to find out the opinion matching or Q-Cochran test. The data collection technique was done by using test instrument. The subjects in this research were the Mathematics experts who consisted of Mathematics lecture, school’s Mathematics teacher and 30 students of VIII at Junior High School 3 Majalengka to identify the problem that students experienced and also with limited trial after the lesson material being implemented. The research design was using development model of ADDIE (analysis, design, development, implementation, evaluation). The result of this research showed there were still some problems which students got after using the learning materials but it was not same with the first trial. The validation on Mathematics module learning material was done by 5 valuators; they were three Mathematics expert lectures from FKIP Unswagati and two Mathematics teachers from Junior High School. Based on validation result, it could be concluded that the learning material of function module with students’ Mathematics comprehension basic ability with using learning model of problem based learning was gotten the merging validation for students’ lesson material for 82% its mean, it was suitable to be used in learning process, whereas for Q-Cochran Test at the students learning material showed that Q count (8) was smaller than Q table (9,488) so Ho was rejected H1 was accepted. It means, there was not different argumentation from significant experts. So, it could be concluded that the learning material was suitable or it could be used/implemented at the learning process. Whereas for teacher’s guidance learning material for 86% it means, it was also suitable to be used in learning process. Whereas for Q-Cochran test at the teacher’s learning guidance that Q count (4) was smaller from Q table (9,488) so Ho was rejected and H1 was accepted. It means, there was not different argumentation from significant experts. So, it could be concluded that teacher’s learning guidance was suitable or it was able to be used/implemented in learning process. The students’ score completeness after doing implementation of learning material was for 20% from 30 students who joined limited experiment test of students’ Mathematics comprehension ability.       Keywords: Mathematics Comprehension Ability, Function, Problem Based Learning